Pharmacokinetic evaluation of Shenfu Injection in beagle dogs after intravenous drip administration - Yuqiao Zhang; Dali Tian; Yuyou Huang; Ling Li; Juan Mao; Juan Tian; Jinsong Ding (Elsevier, 2016)
Shenfu Injection (SFI) is a well-defined Chinese herbal formulation that is obtained from red ginseng and processed aconite root. The main active constituents in SFI are ginsenosides and aconitum alkaloids. In this work, ginsenosides (ginsenoside Rg1, ginsenoside Rb1 and ginsenoside Rc) and aconitum alkaloids (benzoylmesaconine and fuziline) were used as the index components to explore the pharmacokinetic behavior of SFI. A selective and sensitive HPLC-MS/MS method was developed for the quantification of ginsenosides and aconitum alkaloids in dog plasma and was used to characterize the pharmacokinetics of the five index components after intravenous drip of three different dosages of SFI in beagle dogs. The pharmacokinetic properties of the index components were linear over the dose range of 2-8 mL/kg.